Islamic financing and firm performance: evidence from Indonesia - Aiman Aiman; Tastaftiyan Risfandy; Ahmet Faruk Aysan; Bimo Saktiawan (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - This paper analyzes the impact of financing decisions on firm performance. In particular, the effect of Islamic financing on financial profitability. Method - We use a sample of 87 non-financial firms from 2018 to 2022 listed on the Indonesia Stock Exchange and yields 434 observations after selected companies that use Islamic financing as a sample criteria. The data comes from audited annual report and the Osiris database. To analyze the data, this research employs a quantitative method with the random effect regression technique. Result - Our findings shows that Islamic financing can affects firm performance. The firm can use Islamic financing as a strategic financial decision and as alternative source of financing that can improve firm performance. Implication - This paper calls for policymakers, specifically top executive management, to pay more attention to and consider Islamic financing as an alternative to corporate financing in relation with the company's capital structure. Regulators also should encourage and improve regulations to support and facilitate the infrastructure of Islamic finance. Originality - This study expands the empirical studies in finance particularly in the area capital structure.